Aksiologi Sains pada Matematika - Rahmy Zulmaulida; Dhia Salsabila (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
This research investigates the relationship between the axiology of science and mathematics, focusing on values, ethics, and norms in the context of scientific research. The study underscores the importance of integrating the axiology of science into mathematics, highlighting that values and ethics should be integral considerations in the development of mathematical knowledge. The research methodology employed is a comprehensive literature review, exploring the contributions of ethical values to the development of mathematics and the ethical implications in mathematical practice. The results of the study reveal that mathematics is not a separate entity from values and ethics; rather, it is closely intertwined with them. The research details how personal values, scientific values, and social values influence the mathematical research process and its application in various scientific disciplines. Ethical implications in the development of mathematical theory are also a significant focus, considering how ethics affect axiomatic considerations, definitions, and theorems in mathematics. This research suggests that integrating the axiology of science into mathematics is highly relevant for the advancement of mathematical knowledge. It helps mitigate biases, enhances understanding of virtues, raises ethical awareness, and improves the abilities of mathematicians to adhere to values, ethics, and norms in their research. The research findings hold significance in the contexts of mathematical education and practice and in promoting ethical considerations in the use of mathematics in science and society.